Anti-Muslim Attacks - Li, Gang (Religious Violence Today: Faith and Conflict in the Modern World, 2020)

Book Review: Interpreting Islam in China: Pilgrimage, Scripture, and Language in the Han Kitab. By Kristan Petersen - Li, Gang (2019)

Dui qiangzhi weixie funü zui de sikao 對強制猥褻婦女罪的思考 [On indecent assault] - Li, Gang; et al. (甘肃政法大学学报 / Journal of Gansu University of Political Science and Law, 2005)

Dui weihu shaoshu minzu renquan yu fazhi hexie de sikao 對維護少數民族人權與法治和諧的思考 [On minority rights, rule of law and a harmonious society]. - Li, Gang; et al. (西北民族大学学报（哲学社会科学版）/ Journal of Northwest University for Nationalities (Philosophy and Social Science edition), 2005)

Lisiben tiaoyue hou de Oumeng shaoshuren quanli 里斯本條約後的歐盟少數人權利 [EU’s minority rights protection in post-Lisbon treaty]. - Li, Gang (内蒙古大学学报(哲学社会科学版) / Journal of Inner Mongolia University (Philosophy and Social Sciences), 2012)

Reasoning The Sharīʿa and Constructing a Proper Muslim Woman: Reflections on the Issue of Chinese Muslim Women's Haircut in Republican China - Li, Gang (Journal of Chinese Religions, 2022)
The major Muslim group in China, the Hui, discussed the issue of haircut for Muslim women in their own newspapers and magazines in the 1930s. Authors of those publica- tions include ordinary male and female Hui Muslims, Islamic clerics, and Muslim stu- dents from the new Islamic educational institutions. Based on various sources of Islamic jurisprudence (Sharia), the participants put forward varying opinions on the issue. In this article, I have investigated the debate on the Hui women's haircut by assessing how the debate started and developed, and what it meant for a Hui Muslim woman to cut or not to cut her hair in relation to the Shari a in the sociopolitical context of Republican China. I argue that different narratives tried to construct a proper Muslim woman, and furthermore, I also assess how Muslims in China during the Republican period defined their own identities of being Chinese and Muslim via debating on the "authentic" inter- pretation of the Shari' a Finally, Ipoint out that liberation of Chinese Muslim women is impossible unless there is comprehensive participation of them in the debat
CRIS-Team Scopus Importer:2024-12-16
Keywords: Hui Muslims; women in Islam; haircut; Shari' a; Republic of China

The Modernization of Islamic Education in China: The Case of the Hui Muslims - Li, Gang (Bildungskulturen im Islam, 2021)